Free tertiary education does it make economic sense? - Japlos, Jose Gabriel L.; Tan, Chermaine Janise L.; Quimbo, Stella Luz A.; Solon, Orville Jose C. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
This study aims to measure the social benefits of free tertiary education. We measure both private (effects on income) and public benefits (measures of citizenship like propensity to vote, violence against women, payment of taxes and working for the public sector). Using Multiple Linear Regression, we then measured the following_ wages, voter turnout, local tax collected, violence against women and children, and by using a Logit Model, the likelihood of working in the public sector as the determinants of private and social returns of tertiary education. Results suggest that tertiary education provides private benefits in that regions with a higher proportion of SUC graduates are more likely to have increased wages, and less violence against women. Additionally, results show that graduating from an SUC increases the probability of an individual to work in the public sector. Thus, it is clear that in various forms, providing free tertiary education brings about positive private and social returns.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Education, Higher -- Economic aspects -- Philippines